PENDAMPINGAN DAN PELATIHAN PENDAFTARAN HAK CIPTA CONTENT CREATOR YOUTUBE DI SEKOLAH MENENGAH ATAS NEGERI 2 KABUPATEN MERAUKE - Yosman Leonard Silubun; Marlyn Jane Alputila; Jaya Setiawan Sinaga (Musamus Devotion Journal, 2022)
The purpose of carrying out Community Service activities is to increase students' knowledge as YouTube content creators in registering their creations (content). The implementation method used in an effort to achieve the targets and outcomes to be achieved in this Community Partnership Program activity consists of: Field Observation, the first step that must be taken as input in the process of preparing this activity proposal and collecting technical data for the need for the preparation of learning media , Library Studies, which is a step that aims to collect references to the results of academic studies in the form of journals and scientific articles on the procedure for registering copyright. And Planned Activities: Seminar Programs, Workshops and Guidance on the introduction and process of copyright registration with outreach and training activities. The results achieved are an increase in students' awareness and understanding of the awareness to register every creative result of creator content so that their work can be registered so that they get Copyright protection. It will automatically provide legal certainty and legal protection for each registered work. Outcomes of this activity: (1) Journals, (2) Pocket Books on Knowing Copyrights and how to register them.